Strategies to assist uptake of pelvic floor muscle training for people with urinary incontinence: A clinician viewpoint. Issue 8 (24th May 2018) - Slade, Susan C.; Hay‐Smith, Jean; Mastwyk, Sally; Morris, Meg E.; Frawley, Helena
Abstract : Aims: The experiences and information needs of clinicians who use pelvic floor muscle training to manage urinary incontinence were explored. Methods: Qualitative methods were used to conduct thematic analysis of data collected from clinician focus groups and interviews. Participants were registered physiotherapists and continence nurses in Melbourne, Australia. Recruitment was through a combination of purposive and "snowball" sampling and continued until data adequacy was reached. Results: Twenty‐eight physiotherapists and one continence nurse participated in seven focus groups and one interview. The main finding communicated by the participants was that pelvic floor muscle training requires comprehensive descriptions of program details in order for clinicians to implement evidence‐based interventions. The following themes were identified: (1) pelvic floor muscle training tailored to the needs of each individual is essential; (2) training‐specific cues and verbal prompts assist patients to learn and engage with exercises; and (3) clinicians can benefit from research summaries and reports that provide explicit and comprehensive descriptions and decision rules about intervention content and progression. The data indicated that some clinicians can have difficulty interpreting and applying research findings because it is not always well reported. Conclusions: Clinicians who use pelvic floor muscle training to treat urinary incontinence advised can benefit from accessing explicit details of interventions tested in research and reported as effective. They viewed tailoring therapy to individual goals and the use of verbal prompts and visualization cues as important engagement strategies for effective exercise performance. Explicit reporting could be facilitated by using an exercise guideline template, such as the Consensus on Exercise Reporting Template (CERT).